2009
DOI: 10.1007/s10765-009-0621-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Irreversible Cogeneration Systems under Alternative Performance Criteria

Abstract: In this study, an exergy optimization has been performed for a cogeneration plant consisting of an irreversible Carnot heat engine. In the analysis, different objective functions have been defined based on alternative performance criteria and the optimum values of the design parameters of a cogeneration cycle were determined for different criteria. In this context, the effects of irreversibilities on the exergetic performance are investigated, and the results are discussed. List of SymbolṡE Exergy ratė Q Rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 13 publications
(17 reference statements)
1
6
0
Order By: Relevance
“…These results gives a more general upperbound for the exergetic efficiency compared to the results given by Erdil [29] and Atmaca et al [30] due to the fact that finite heat source and sink have been considered here, but without heat leakage (adiabatic case). This will be considered in the future.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…These results gives a more general upperbound for the exergetic efficiency compared to the results given by Erdil [29] and Atmaca et al [30] due to the fact that finite heat source and sink have been considered here, but without heat leakage (adiabatic case). This will be considered in the future.…”
supporting
confidence: 56%
“…The set of equation is adapted to take account of system internal irreversibilities, according to entropy analysis or experimental identifications. The obtained results are not limited to linear heat transfer law, or by the fact that the model imposes to introduce two irreversibility ratios [29,30]. We reiterate that it has been proposed in preceding papers that the entropy analysis method preferable to the ratio method [33,34].…”
Section: Generalizationmentioning
confidence: 51%
“…The majority of the work produced by the turbine (work produced by the turbine to the compressor is called back work rate and is around 50-60 %) is spent by the compressor so that the pressure ratio (compressor work) are very effective on the cycle efficiency (Najjar, 2001;Atmaca et al, 2016). Many publications are based on finding better evaluation criteria and the most effective parameters on efficiency for gas turbine cogeneration cycle (Atmaca et al, 2009;Atmaca, 2011). These studies generally contain fewer criterions, parameters and cycles therefore they are not satisfactory as a rule of thumb.…”
Section: Introductionmentioning
confidence: 99%
“…Erdil (2005) investigated the Downloaded by [University of Guelph] at 01:10 11 October 2012 optimal exergetic output rate and exergetic efficiency performance of an irreversible combined Carnot cycle cogeneration plant with heat resistance, heat leakage and internal irreversibility and concluded that the performance is independent of the consumer-side temperature. Atmaca et al (2009) investigated the optimal exergetic output rate, energy utilization factor, artificial thermal efficiency and exergetic efficiency performance of an irreversible Carnot cycle cogeneration plant. Yilmaz (2006) optimized the exergy output rate of an endoreversible simple gas turbine closed-cycle cogeneration plant with the sole irreversibility of heat resistance by optimizing the temperature ratio of the working fluid and concluded that the lower the consumer-side temperature, the better the performance.…”
Section: Introductionmentioning
confidence: 99%